Effect of actionable somatic mutations on racial/ethnic disparities in head and neck cancer prognosis. Issue 8 (29th March 2016) - Wu, Evan S.; Park, Jong Y.; Zeitouni, Joseph A.; Gomez, Carmen R.; Reis, Isildinha M.; Zhao, Wei; Kwon, Deukwoo; Lee, Eunkyung; Nelson, Omar L.; Lin, Hui‐Yi; Franzmann, Elizabeth J.; Savell, Jason; et al.
Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide and minorities have the worst survival. However, the molecular mechanisms underlying survival disparities have not been elucidated. Methods: In a retrospective study, we assessed association between HNSCC early death (<2 years) and 208 somatic mutations of 10 cancer‐related genes in 214 patients: 98 non‐Hispanic whites (46%), 72 Hispanic whites (34%), and 44 African Americans (20%). Results: Hispanic whites and African Americans had significantly higher mutation rates for EGFR, HRAS, KRAS, and TP53 . HNSCC early death was significantly associated with 3+ mutations (odds ratio [OR] = 2.78, 95% confidence interval [CI] = 1.16, 6.69), NOTCH1 mutations in non‐Hispanic whites (OR = 5.51; 95% CI = 1.22–24.83) and TP53 mutations in Hispanic whites (OR = 3.84; 95% CI = 1.08–13.68) in multivariable analysis adjusted for age, sex, tumor site, and tumor stage. Conclusion: We have provided the proof‐of‐principal data to link racial/ethnic‐specific somatic mutations and HNSCC prognosis and pave the way for precision medicine to overcome HNSCC survival disparities. © 2016 Wiley Periodicals, Inc. Head Neck 38:1234–1241, 2016